The macrostructure of the text in teaching process: it can be a support or an obstacle in the meaning construction during school learning - Antić, Slobodanka (Psihološka istraživanja, 2024)
The contemporary circumstances of teaching and learning at all levels of education, as well as the easy availability of a variety of learning resources, force teachers to expand textual learning resources. This leads to the need to analyze the role of the text in teaching practice. Text in teaching practice is a broader category of teaching material in which textbooks are a subcategory. Given that learning in a formal context is mainly based on verbal content and literacy practice, it is very important to look at different aspects of the text, i.e. evaluate their potential for learning. The aim of this work is to map the characteristics of the macrostructure of the text in teaching practice, which are important for the improvement of the zone of meaning construction during school learning. The paper presents the concept of text macrostructure, analyzes the similarities and differences of the concepts of text type, genre, and discourse, and provides an overview of research that links text macrostructure and its effects on learning. Finally, pedagogical implications are drawn. The macrostructure of the text from which one learns must become a relevant factor for lessons planning, evaluating the success of learning, but also improving educational policy, including teacher education.
Keywords: text in teaching practice, macrostructure of school text; school text discourse; construction of sense and meaning; reading comprehension